(untitled) (Research, Society and Development, 2023)
Currently, there is a serious water crisis caused by anthropogenic issues. It is extremely important to understand how anthropic activities influence the quality of aquatic ecosystems from the perspective of restoring degraded ecosystems, aiming to restore their ecological integrity. The objective of this work research was to analyze the biological effects of water pollution in the Itapecuru river in the city of Caxias-Ma. For the collection of water samples, five points were chosen, being described in P1, P2, P3, P4 and P5, from the upstream downstream on the banks of the Itapecuru river. The collections were made in two periods, between “November and December” and the rainy period “May”. The water samples were taken to the Physical-Chemistry Laboratory of SAAE (Autonomous Water and Sewage Service) for physical-chemical analysis. The waters of the Itapecuru River are polluted in the collected areas. They had a high iron content, yellowish color and turbidity in both analyzed periods. Despite the absence of heavy metals in the analyzed water, the possibility of its toxic potential is not ruled out.